2012
DOI: 10.1007/s00268-012-1853-0
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Nerve Injury with Unexpected EMG Signal Recovery in Thyroid Surgery Using Continuous Intraoperative Neuromonitoring

Abstract: Only continuous VN stimulation serves to detect early changes in EMG response that indicate imminent danger to RLN functional integrity and alerts the surgeon to immediately correctable surgical actions, thus possibly preventing nerve damage or transforming damage into a reversible event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 13 publications
(23 reference statements)
1
60
0
1
Order By: Relevance
“…CIONM may be more accurately described as repeated pulsed stimulation that is contemporaneous with the surgical maneuvers (11). The possible advantage of a CIONM format is that it has the potential to monitor the entire vagus and RLN functional integrity in real-time throughout surgery and could identify EMG signals associated with early-impending injury states (8,9,11,(15)(16)(17)(18). As shown by Schneider et al (19) the final outcome of RLN dysfunction was significantly improved by CIONM.…”
mentioning
confidence: 99%
“…CIONM may be more accurately described as repeated pulsed stimulation that is contemporaneous with the surgical maneuvers (11). The possible advantage of a CIONM format is that it has the potential to monitor the entire vagus and RLN functional integrity in real-time throughout surgery and could identify EMG signals associated with early-impending injury states (8,9,11,(15)(16)(17)(18). As shown by Schneider et al (19) the final outcome of RLN dysfunction was significantly improved by CIONM.…”
mentioning
confidence: 99%
“…Previous investigations pointed out that the change in signal quality during other surgical procedures (signal loss or reduction in amplitude below 50%) could be the result of traction and distension of nervous tissue indicating postoperative nerve palsy [13,14]. Continuous pIONM in a consecutive series of fourteen pigs was found to result in variable amplitude levels during low anterior rectal resection, which underlines the existence of several confounding factors and thus even more the importance of a standardized pIONM procedure [15].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, an observational study of 1,526 patients confirmed that operation with CIONM resulted in fewer permanent VF palsies compared with intermittent IONM (0 vs. 0.4%; P=0.019) after thyroid surgery in patients with benign disease (4). CIONM helps detect adverse EMG changes early on and prevent severe RLN injuries that cause LOS by permitting the surgeon to release distressed nerves (20,45,46). RLN injury comes in two varieties, which differ in many ways (47):…”
Section: Challenges Of Preventing Rln Palsy Under Ionmmentioning
confidence: 99%